Reasons for the Street Girl’s Entry into Commercial Sex Work: A Case Study of the Harare Central Business District, Zimbabwe (RSGECSWH - Chikoko, Witness; Ruparanganda, Watch; Muzvidziwa, Victor N.; Chikoko - Chimhowa, Emelia (Kamala-Raj Enterprises, 2021)
The paper problematicises the reasons why the street girls of the Harare Central Business District enter or engage in transactional or commercial sex work. Drawing from a child agency theory, street girls demonstrated their agency through trading in commercial sex work. The entry of street girls into commercial sex work also constitutes ambiguity of agency. The behaviours of these street girls also illustrate self-destructive agency. On the other hand, the entry of street girls into commercial sex work also highlighted huge child rights violations prevalent on the streets of the Harare Central Business District. The research findings suggest that the reasons why the street girls of the Harare Central Business District enter into commercial sex work are multiple and varied. The qualitative research methodology involving the street ethnography was used in this study. The paper also recommends full implementation of child rights laws, policies and programmes so as to arrest commercial sex work among street girls.